Osteomyelitis of phalanx and salvage using the Masquelet technique - Giri, Piyush; Kunwar, Sushma; Khadka, Karuna; Pokhrel, Shrinkhala; Pandey, Pratishtha (Journal of Patan Academy of Health Sciences, 2024)
A fingertip has precise functional roles of fine movement, touch, and sensory functions. Its injury majorly hampers not only the functional aspect but also carries great aesthetic significance. Osteomyelitis is a serious bone infection that presents a complex clinical challenge that demands a multidisciplinary approach. The integration of antimicrobial therapy, surgical intervention, and bone reconstruction is often considered the mainstay of treatment. We report a case of osteomyelitis of finger management and bony defect reconstruction using the Masquelet technique for good functional outcome and preservation of the finger.